2012
DOI: 10.1021/nn303126n
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pore Geometry in Single Nanoparticle Detection

Abstract: We observe single nanoparticle translocation events via resistive pulse sensing using silicon nitride pores described by a range of lengths and diameters. Pores are prepared by focused ion beam milling in 50 nm-, 100 nm-, and 500 nm-thick silicon nitride membranes with diameters fabricated to accommodate spherical silica nanoparticles with sizes chosen to mimic that of virus particles. In this manner, we are able to characterize the role of pore geometry in three key components of the detection scheme, namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
158
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(163 citation statements)
references
References 48 publications
(86 reference statements)
5
158
0
Order By: Relevance
“…They found that a constant AR assumption tted their experimental measurements well. Under the hypothesis of invariant AR and a, Davenport et al 22 systematically investigated the role of nanopore geometry in nanoparticle experiments using different aspect ratio nanopores. However, constant AR might not be able to predict the current change correctly in some cases, especially when particle's diameter is larger than pore's length.…”
Section: -15mentioning
confidence: 99%
See 2 more Smart Citations
“…They found that a constant AR assumption tted their experimental measurements well. Under the hypothesis of invariant AR and a, Davenport et al 22 systematically investigated the role of nanopore geometry in nanoparticle experiments using different aspect ratio nanopores. However, constant AR might not be able to predict the current change correctly in some cases, especially when particle's diameter is larger than pore's length.…”
Section: -15mentioning
confidence: 99%
“…We then compared our numerical results with the experimental data of Bacri et al 36 and Davenport et al, 22 as shown in Table 1. This table also lists the results of two other analytical models: (i) the model without AR, which only considers the resistance change inside the pore, is used in the work of Bacri et al, 36 and (ii) the model with constant AR, which is the results of the no AR model divided by (1 + a o ), is similar to the approximate formula used in the work of Davenport et al 22 Our numerical results give more accurate values than the model without AR.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a), partial pore blocking (V > 0) and unblocking (V < 0) occur when the migration (MIG) flow resulting from the particle surface charge and the electro-osmotic (EOF) flow resulting from the pore surface charge act in concert, reinforcing the rectification effect. 14,15,25 This mechanism is also shown in Fig. 1(b), with the trivial change in the sign of the blocking (V < 0) and unblocking (V > 0) voltages with respect to Fig.…”
mentioning
confidence: 54%
“…Note that models for blocking predict high electric fields in the solution close to the pore mouth. 14,19,25 Single, approximately cylindrical pores are obtained in 12 lm thick polyethylene terephthalate membranes using track-etching procedures. Fig.…”
mentioning
confidence: 99%